Deskripsi Masalah Belajar Peserta Didik pada Pembelajaran Tematik Pasca Covid-19 di Kelas V - Sekar Dewi; Budiman Tampubolon; Hery Kresnadi; Rio Pranata (AS-SABIQUN, 2023)
This study aims to describe the learning problems experienced by students in post Covid-19 thematic learning in class V elementary school. The research method used is descriptive with a qualitative research type. The data sources for this research were fifth grade students. Data collection techniques used direct and indirect communication techniques with questionnaires and interviews as research instruments. The results showed that the learning problems experienced by students were caused by internal factors, namely from the indicators of the characteristics of students, namely not having an interest in learning, ignoring learning readiness. Indicators of attitudes toward learning are not paying enough attention to the learning process. From the indicators of learning concentration, namely difficulty concentrating while studying. An indicator of self-confidence is a lack of confidence in doing tasks. Indicators of study habits are studying only before exams/tests, and studying in a hurry. While the learning problems experienced by students were caused by external factors, namely from the teacher's indicator, the teacher was less familiar with students, did not appreciate students in learning. The family (home) indicator is a less harmonious family. Social environmental indicators (peers) namely environmental conditions are inadequate. Indicators of facilities and infrastructure are the lack of equipment to support the learning process, as well as inadequate classroom conditions. For the most dominating factor is from internal factors there is an indicator of study habits. Meanwhile, from external factors, the most dominating indicator is the teacher's indicator.